Improving Delivery of Construction Projects in Ghana’s Cities: A Lean Construction Approach - Salifu-Asubay, Emmanuel Kwaku; Adjei Mensah, Collins (International Journal of Sustainable Construction Engineering and Technology, 2015)
The construction industry plays a vital role in the physical and socio-economic development of cities. However, poor execution and frequent breakdown of construction works such as roads and houses obstruct the overall development of cities since most social and economic activities depend of these projects. This paper sought to assess the extent to which lean construction principles are utilised in construction activities in Ghana’s cities and ways that these principles can be applied effectively to improve the delivery of construction works. The study concentrated in Accra, Kumasi and Sekondi-Takoradi cities whilst officials from the Metro Works Departments of the selected cities and various construction professionals constituted the target population. Questionnaire was the research instrument employed and Spearman Rank Correlation Coefficient Test was used to analyse the results. It was revealed that various lean construction principles such as value, value stream, flow, pull and perfection are poorly implemented with each of these principles having less than 50 percent rate of application. Barriers such as long lead time, poor procurement system and contracts, cultural and human factors, political influence, and lack of financial and management commitment were found to be responsible for that. To successfully apply the lean construction principles and enhance the sustainability of construction projects, measures such as benchmarking, process mapping, last planner procedures and continuous training of workers in the construction industry have been recommended.